Analysis of The Effect of Asset Quality, Liquidity, Independent Board of Commissioners, Sharia Supervisory Board on Profitability (Study on Islamic Commercial Banks Registered With OJK In 2017-2023) - Fajar, Muhammad; Nuryaman, Nuryaman (Dinasti Publisher, 2024)
This study examines the effect of Financing To Deposit Ratio (FDR), Non-Performing Financing (NPF), and Good Corporate Governance (GCG) on the Profitability (ROA) of Islamic commercial banks listed on the Financial Services Authority for the period 2017-2023. The independent variables used are NPF, FDR, and GCG which are proxied by the ratio of the number of independent commissioners and the number of commissioners and the frequency of Sharia Supervisory Board meetings. The dependent variable used is the return on assets (ROA). The results of this study indicate that Non-Performing Financing (NPF) has an effect on profitability (ROA), while Financing To Deposit Ratio (FDR), Independent Board of Commissioners (DKI), and Sharia Supervisory Board (DPS) have no significant effect on the profitability of Islamic commercial banks.